1996
DOI: 10.1097/00007890-199611150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Superoxide Dismutase and Polyethylene Glycol-Linked Superoxide Dismutase Against Renal Warm Ischemia/Reperfusion Injury

Abstract: The protective effect of oxygen free radical scavenger superoxide dismutase (SOD) against the warm ischemic damage that occurs in kidneys harvested from non-heart-beating donors is controversial because of its short half-life. In this model, we compared the protective effect of SOD and two longer lasting polyethylene glycol (PEG)-linked forms of SOD in a model of renal ischemia induced by 60 min of arterial clamping in rats. Rats treated with PEG1-SOD and PEG2-SOD had a better renal function than controls, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…injury [3,29]. The decrease in renal CAT, SOD and GSH-Px activities is probably the result of the inactivation by ROS produced by I/R.…”
Section: Discussionmentioning
confidence: 99%
“…injury [3,29]. The decrease in renal CAT, SOD and GSH-Px activities is probably the result of the inactivation by ROS produced by I/R.…”
Section: Discussionmentioning
confidence: 99%
“…If free radical mediated lipid peroxidation remains uncontrolled, cell death will ultimately result. Experimentally various antioxidant agents such as superoxide dismutase, catalase, allopurinol, iloprost, and calcium channel blockers were used to prevent kidney from IR injury [1,3,11,12]. The role of reactive oxygen species in human kidney transplantation seems to correlate with results obtained in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that in unilaterally nephrectomized rats, a 45-or 60-min ischemia period by clamping the renal pedicle results in ATN and a four-to fivefold increase in creatinine levels at the end of a 24-hour follow-up period [1,5,11,12]. In our experimental model, the plasma creatinine levels were elevated in the IC group as compared with the sham group at the end of the 75-min ischemia and 24-hour reperfusion periods (p !…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil activation at sites of injury results in a large production of •O 2 -, which in turn contributes to tissue damage seen post-reperfusion in several ischemic organs including: kidneys (76), stomach (114), skin (34), and heart (3). Cu/Zn-SOD prevents vasogenic brain edema after several kinds of injuries (60), suggesting that •O 2 -is an important factor for blood-brain barrier disruption (62).…”
Section: Ischemia/reperfusionmentioning
confidence: 99%
“…Important tissue damaging and pro-inflammatory roles attributed to •O 2 -include: endothelial cell damage and increased microvascular permeability (20,39,111), formation of chemotactic factors such as leukotriene B 4 (18,23), recruitment of neutrophils at sites of inflammation (10,94,95), lipid peroxidation and oxidation, and single-strand DNA damage (19). Superoxide anion radicals contribute to post-ischemic reperfusion tissue damage demonstrated in several organs (3,34,37,76,115 …”
mentioning
confidence: 99%